Determination of running performance in young soccer players - Karakulak, İzzet (Progress in Nutrition, 2020)
Study Objectives: This study aimed to determine the relationship between running performances in young soccer players and various parameters. Methods: The study was conducted with 20 male athletes from the U-14 youth setup soccer team of a sports club playing in the Turkish Football Super League. Various measurements were made to determine athletes’ height, body weight, leg, lower leg and upper leg length, leg force, active and squat jump heights, sprint times in 15, 20, 25, 30, 35, and 40 meters. The videos, on which athletes’ two full stride lengths where they reached maximal speed were recorded, were analyzed on Ariel Performance Analysis System (APAS) package program the with below-waist analysis method, and their stride lengths on maximal speed were found. Thus, athletes’ step frequencies were found by dividing their running times into their stride lengths. Data were evaluated on SPSS 22.0 package program with descriptive statistics and Spearman’s rank correlation coefficient to determine the correlation between stride length and step frequency, and other parameters. Results: The results of statistical analyses showed that there was a negative medium level correlation between stride length and sprint time in 15m (r=-.484) while there was a negative strong correlation between stride length and step frequency (r=-.880). There was a positive strong correlation between step frequency and sprint time in 15m (r=.751), 20m (r=.691), 25m (r=.632) and 40m (r=.635) while a positive medium level correlation with sprint time in 35m (r=.460). Conclusion: Stride length is more determinative than step frequency especially in short distance races in terms of running performance in young soccer players.